2012
DOI: 10.1371/journal.pone.0038693
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Individual and Environmental Factors to Physical Activity Level among Spanish Adults

Abstract: BackgroundLack of physical activity (PA) is a major risk for chronic disease and obesity. The main aims of the present study were to identify individual and environmental factors independently associated with PA and examine the relative contribution of these factors to PA level in Spanish adults.Methodology/Principal FindingsA population-based cross-sectional sample of 3,000 adults (18–75 years old) from Gran Canaria (Spain) was selected using a multistage stratified random sampling method. The participants we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 75 publications
3
15
0
5
Order By: Relevance
“…We demonstrated that participants with university ed-ucation have a higher level of PA compared to those with a pre-college education; this was similar to results of studies in Spain and Oman (22,23). It seems that academic education improves the knowledge of participants about the benefits of PA. Students were significantly less active than individuals who were unemployed in the current study.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…We demonstrated that participants with university ed-ucation have a higher level of PA compared to those with a pre-college education; this was similar to results of studies in Spain and Oman (22,23). It seems that academic education improves the knowledge of participants about the benefits of PA. Students were significantly less active than individuals who were unemployed in the current study.…”
Section: Discussionsupporting
confidence: 86%
“…The level of PA was higher in unemployed participants than employers, however, not to a significant extent in this study. Some studies have revealed that employment is a risk factor for inactivity (22).…”
Section: Discussionmentioning
confidence: 99%
“…políticas saludables; Keating, Guan, Piñero, & Bridges, 2005). De los factores individuales, la literatura científica muestra que la identificación de las barreras para la realización de la AF, debe ser uno de los objetivos prioritarios para facilitar una conducta más activa entre los universitarios (Serrano-Sánchez, LeraNavarro, Dorado-García, González-Henriquez, & Sanchis-Moysi, 2012). En este sentido, algunos estudios en población universitaria encontraron que las barreras para la realización de práctica de AF se relacionan negativamente con los niveles de AFMV (e.g.…”
unclassified
“…Además, ayudaban a resolver algunas dudas y dificultades que se suelen presentar cotidianamente. El instrumento fue aplicado en dos oportunidades a un De hecho, algunos estudios efectuados en adolescentes han señalado que existe una tendencia a la disminución progresiva de los niveles de AF conforme la edad avanza [9][10][11] , inclusive otros estudios sostienen que se acentúa más entre la última fase de la adolescencia y en la primera fase de la adultez 12,13 , lo cual, es producto de reducidos niveles de actividad física, sedentarismo y mayor consumo de grasas en sus dietas durante los años de estudio 14 .…”
Section: Procedimientosunclassified